已知d>c a+b=c+d a+d

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/27 16:04:25
已知d>c a+b=c+d a+d
x}QAN0nT_E@%*U *@@P_ vNA8ewgwf<ѕ Vǯnw2fN^t,M[ϚpteX-` q8neQc&33}ub +5K㮽 dq(`Hm $J؅x5]sj[H&ӑT>fW^b x=r)֓QעD wyU-c1& 8x ^K$AQjȦǽeTdo'pE5

已知d>c a+b=c+d a+d
已知d>c a+b=c+d a+d

已知d>c a+b=c+d a+d
d>c b+c>a+d 不等式相加可得b+c+d>a+d+c消去同项,可得b>a
由a+b=c+d得d=a+b-c 1式 b=c+d-a 2式
1式代入d>c得a+b>2c
2式代入b>a 得c+d>2a
得出的两个不等式相加得
a+b+c+d>2a+2c而a+b=c+d
可知2c+2d>2a+2c即2d>2a 所以d>a
2a+2b>2a+2c即2b>2c 所以b>c
a+b=c+d可得a-c=d-b
而a+d

a+b=c+d,a+d2a+d+b又a-c=d-b<0得da

a>b>d>c